Go in! Go out! Inducible control of nuclear localization - Di Ventura, Barbara; Kuhlman, Brian (Current opinion in chemical biology, 2016)
Cells have evolved a variety of mechanisms to regulate the enormous complexity of processes taking place inside them. One mechanism consists in tightly controlling the localization of macromolecules, keeping them away from their place of action until needed. Since a large fraction of the cellular response to external stimuli is mediated by gene expression, it is not surprising that transcriptional regulators are often subject to stimulus-induced nuclear import or export. Here we review recent methods in chemical biology and optogenetics for controlling the nuclear localization of proteins of interest inside living cells. These methods allow researchers to regulate protein activity with exquisite spatiotemporal control, and open up new possibilities for studying the roles of proteins in a broad array of cellular processes and biological functions.
Gesehen am 07.05.2020